PENERAPAN STRATEGI PEMBELAJARAN KREATIF-PRODUKTIF TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SEMESTER GENAP SMP PGRI 3 BANDAR LAMPUNG - Rahmawati, Fitriana (Lentera: Jurnal Ilmiah Kependidikan, 2016)
The objective of this research was knowing whether or not there is a difference between students’ learning outcomes in Mathemathics who used productive-creative learning strategy towards students’ learning outcomes in Mathemathics who used conventional learning model. The sample consited of 2 classes, that is VII H as an experimental class and VII G as a control class. The data was measured by using essay test consisting 5 questions. For testing the hypothesis, t-test is used with testing the normality and homogeinity firstly. The result of hypothesis testing using statistical formula obtained tcal = 3,207 from the total distribution t in the significant level 5% =2,00 and = 1,67, while the result of hypothesis testing based on SPSS programme using T independent Sample Test is tcal = 3.224.